1994
DOI: 10.1029/94jd00288
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological and electrical aspects of winter thunderclouds

Abstract: The winter thunderclouds that frequently visit the southeastern coastal area of the Japan Sea were investigated by the field work, operating radars, the sferics direction‐finder system, and the field‐mill network. The clouds take the dipole electrical structure at their developing stage and then take the tripole structure at the mature stage. However, the period covering both dipole and tripole structures is very short (usually less than 10 min in early or late winter and less than several minutes in midwinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 6 publications
5
101
1
Order By: Relevance
“…[20] Kitagawa and Michimoto [1994] reported that the surface electric field often indicates a strong positive value under the weak echo or the SCRWDE. They observed snowflakes and ice crystals under the stratiform region.…”
Section: Where Are Large Positive Electric Charges Removed?mentioning
confidence: 99%
See 1 more Smart Citation
“…[20] Kitagawa and Michimoto [1994] reported that the surface electric field often indicates a strong positive value under the weak echo or the SCRWDE. They observed snowflakes and ice crystals under the stratiform region.…”
Section: Where Are Large Positive Electric Charges Removed?mentioning
confidence: 99%
“…Secondly, winter thundercloud systems often generate +CGs that remove large amounts of charge in spite of low lightning activity [Brook et al, 1982]. The percentage of +CGs (30 -50% per month) in winter is higher than in summer (almost less than 10%) [Kitagawa and Michimoto, 1994], and so it was expected that winter sprites might be produced by thundercloud systems around the Hokuriku region of Japan [Price et al, 2002;Takahashi et al, 2003]. As expected, the winter sprite in this region was first discovered in 1998 [Fukunishi et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…These facts suggest there are two types of atmospheric electrical structure to the cumulonimbus clouds over all the regions, i.e., cumulonimbus clouds with VS lightning and some without. It is well known that there are two types of cumulonimbus clouds that cause winter lightning around the Hokuriku district (region C1) and ordinary summer lightning (Krehbiel et al 1983;Kitagawa and Michimoto 1994). Kitagawa (1996) highlighted the fact that the duration of the dipole and tripole electrical structures is very short in the developing and mature stages of winter thunderstorms, and suggested that these electrical strucdetermine the features of lightning over the Japanese archipelago and the surrounding area (20−55°N, 110−180°E; see Fig.…”
Section: Features Of the Distribution Of Lightningmentioning
confidence: 99%
“…Little research has been carried out on winter thunderstorms in the Netherlands; a larger amount of research has been done in Japan. Kitagawa and Michimoto (1994) for instance describe the meteorological conditions and characteristics of Japanese winter thunderstorms. The most important feature is that thunderstorm clouds in winter are less deep than in summer, so the convective activity takes place at lower heights.…”
Section: Introductionmentioning
confidence: 99%